Peer Helpers’ Experience of Participation in an Adventure-Based Experiential Learning Program: A Grit Perspective - Marica Pienaar; Johan C. Potgieter; Cornelia Schreck; Ilana Coetzee (Frontiers in Psychology, 2022)
The study focused on the adventure-based experiential learning (ABEL) component of the North-West University peer helper training program. The aim of this study was to explore and describe a group of peer helpers’ subjective experiences of their participation in an ABEL program, with a focus on how these experiences related to the concept of grit. A total of 26 students at the North-West University, both male and female, participated in the study. A qualitative research approach with a case study research design was used. The participants completed daily reflective diaries for the duration of the three-day ABEL program. After 3 months of performing their duties as peer helpers, the same individuals participated in focus group interviews. Themes were identified through inductive analysis and discussed regarding their relevance to the concept of grit. The main themes that emerged from both phases of data collection included intra-, inter-, and transpersonal/transcendent aspects, within which participants regularly referred to elements of grit. It was concluded that ABEL, due to its unique nature and demands, provides an ideal mechanism for the facilitation of personal growth on various levels. More specifically, through its clear association with the improvement and/or development of participants’ grit, it could equip these students to be more effective in their role as peer helpers.